Atividade física como moderador da disfunção endotelial em pessoas com transtorno depressivo: uma revisão sistemática com meta-análise - Waclawovsky, Aline Josiane (2020)
Depressive disorder, or depression, is a highly prevalent mood disorder and associated with an increased risk of developing cardiovascular disease. Endothelial dysfunction can be an early indicator of cardiovascular disease risk. However, there is still no consistency in the literature on how much people with depression have endothelial dysfunction and how much physical activity can moderate this association. The objectives of the dissertation were to review the literature and summarize the studies that compared the presence of endothelial dysfunction between people with depression versus people without depression and to explore whether physical activity moderates this association. A systematic review with comparative meta-analysis was carried out. The search for studies that evaluated endothelial function using the flow-mediated dilation technique (FMD) in people with depression and controls was carried out in four databases: PubMed, Embase, Web of Science and PsycINFO, from the beginning of the databases to February 27, 2020. Meta-analyzes of random effects were performed and heterogeneity was explored through meta-regressions and subgroup analyzes. the search resulted in a total of 5,188 studies and of these 9 were included because they met the inclusion criteria of the present study. These 9 studies included a total of 1,367 participants, with a median age of 39.8 years, with a median of 44.9% men. People with depression have 1.92% lower FMD (N=9, MD= -1,92, IC 95% -3,12 a -0,72, p<0,002, I2=93,31) when compared to controls. There is no difference in endothelium-independent vasodilation (N=7, MD= -0,691, IC 95% -1,790 a 0,408, p= 0,218, I2=61,5%). HDL levels, explored by meta-regression, explained 45% of the difference found. In the subgroup analyzes, people whose depression was confirmed by diagnostic instruments had impaired endothelial function when compared to controls, with a 3% less dilation (N= 4, MD= -3,339, IC= -5,415 a -1,264, p= 0,001, I2= 89,3). People with depressive symptoms have no difference in FMD when compared to controls. Still, in the studies that evaluated FMD in the first minute after release of the occlusion , there was a difference between depressed and controls (N= 5, MD=-3,090, IC= -4,777 a -1,404, p= 0,000, I2= 85,7). There is a difference in endothelial function when using the occlusion position in the distal forearm (N= 3, MD= -4,390, IC= -6,607 a -2,172, p= 0,000, I2= 80,1) and when using occlusion pressure between 250 to 300 mmHg (N= 4, MD= -2,445, IC= -4,274 a -0,616, p= 0,008, I2= 87,1). Conclusion: Individuals with depression have endothelial dysfunction when compared to controls. These findings may have clinical implications, as the reduction in FMD is an early marker of cardiovascular risk and can be a diagnostic strategy to enhance the care and attention to cardiovascular health of people with depression.